Understanding the Dangers of E-Cigarettes Through Information Services - Fajriani, Indah; Masya, Hardiyansyah; Ogdalina, Putri (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2024)
An electronic cigarette is a device designed to deliver nicotine without tobacco acid by heating a solution of nicotine, flavoring, propylene glycol and glycerin. This research is motivated by the fact that there are still many students at junior high schools (MTsN 3 North Lampung) who have a low understanding of the dangers of electronic cigarettes because lack of provision of information services. This research aims to determine the effect of information services in increasing understanding of the dangers of e-cigarettes among students at junior high schools (MTsN 3 North Lampung). The research method used is a quasi-experimental method with a Non-equivalent Control Group Design. The instrument used is a questionnaire or questionnaire. The population in this study was 60 students, namely class VIII. The research results show that there is a significant influence on information services to increase understanding of the dangers of e-cigarettes among students at MTsN 3 North Lampung.